The professionalising of breast feeding—Where are we a decade on? - Fenwick, J; Sheehan, A; Barclay, L; Burns, E; Schmied, V; Rolfe, M; Longman, J (My University, 2012)
This paper is an empirically informed opinion piece revisiting an argument published in Midwifery 10 years ago, that the increasing professionalisation of breast feeding was not supporting women in Australia in sustaining breast feeding. We present the last 10 years of primary research on the topic, explore major policy initiatives and the establishment and growth of lactation consultants in Australia to see if this has made a difference to sustained rates of breast feeding. We present an analysis of the only consistently collected national statistics on breast feeding and compare this with national and state level government data collections from the last decade. We have found that the considerable effort invested in trying to improve duration of breast feeding amongst women in Australia appears to have failed to improve sustained breast-feeding rates. We argue that this situation might be related to losing sight of the embodied nature of breast feeding and the relationships that must exist between the mother and baby, the knowledge and skills women quickly develop, and a loss of woman to woman support. We conclude that midwives have a major role in avoiding us reproducing similar, unintended, negative consequences to those resulting from increasing obstetrician managed normal birth. These include midwifery scrutiny and involvement in policy development and institutional practices and the design of services.
Keywords: Health -- Access to services; Policy; Health -- Breastfeeding; Government, law and policy; Health and wellbeing; Policy; Health; Access to services; Breastfeeding; Health and wellbeing; Government, law and policy